STRATEGI DAN IMPLEMENTASI BUDAYA RELIGIUS DALAM MEMBANGUN KARAKTER SISWA - ZAINUDDIN ZAINUDDIN; MUSTAFIYANTI MUSTAFIYANTI; MUHAMMAD MUTTAQIN (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
Abstract : This study aims to identify and describe the strategy and implementation of religious culture in schools. This research is a descriptive study using a qualitative approach. Data collection methods used include: a) in-depth interviews; b) participatory observation (participant observation); and c) documentation. Furthermore, the data collected through the three techniques were organized, interpreted, and analyzed repeatedly, to be analyzed using data analysis techniques, namely by presenting data, reducing data, and drawing conclusions. The findings of this study are that in the process of creating a religious culture, because of the socialization process carried out by the principal and all school members in realizing the vision, mission, goals and ideals of the school to the fullest. In the process of forming a religious culture, it is carried out through the stages of planning, implementation and supervision. The forms of religious activities that can be implemented include Tadarus al-Qur'an, Implementation of Dhuha Prayers, Implementation of Dhuhur Prayers in congregation, hospitality, getting used to the 3S culture (smiles, greetings and greetings), Berinfaq and giving alms, and commemoration of religious holidays.